2020
DOI: 10.1016/j.econmod.2020.04.024
|View full text |Cite
|
Sign up to set email alerts
|

The role of Provincial Government Spending Composition in growth and convergence in China

Abstract: China's development policy since 1978 has differed across regions. With rapid aggregate growth has come widening regional inequality. The 1994 fiscal decentralisation reforms shifted political pressure onto provincial officials to boost local growth through local public investments. These investments affect regional convergence by counteracting regulatory frictions in factor accumulation, and can also determine steady-state growth. However, the effect of public spending allocations across physical and human ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 63 publications
0
7
0
2
Order By: Relevance
“…To test whether the economic growth of a country or region converges in the real world, scholars have conducted a lot of empirical studies. Most of the research conclusions support the existence of economic growth convergence (Cheng et al,2020;Luintel et al,2020;Startz,2020).…”
Section: Introductionmentioning
confidence: 79%
“…To test whether the economic growth of a country or region converges in the real world, scholars have conducted a lot of empirical studies. Most of the research conclusions support the existence of economic growth convergence (Cheng et al,2020;Luintel et al,2020;Startz,2020).…”
Section: Introductionmentioning
confidence: 79%
“…In the 1980s and 1990s, state investments in the rural areas accounted for less than 10% of the budget, despite the fact that the rural population made up approximately 75% of the national population at that time (Yang, 1999). The regional inequality resulted from spatially differentiated development policy, which was openly acknowledged by Deng Xiaoping in his Southern Tour of 1992: “If all of China is to become prosperous, some areas must get rich before others.” It was hoped that the development of the eastern regions would lead to regional trickle down rather than long‐term divergence (Luintel et al, 2020).…”
Section: China's Hukou System and Urban Biasmentioning
confidence: 99%
“…The regional inequality resulted from spatially differentiated development policy, which was openly acknowledged by Deng Xiaoping in his Southern Tour of 1992: "If all of China is to become prosperous, some areas must get rich before others." It was hoped that the development of the eastern regions would lead to regional trickle down rather than long-term divergence (Luintel et al, 2020).…”
Section: The Rationale Of the Hukou Systemmentioning
confidence: 99%
“…Some studies show that regional government spending increases economic growth (Deviani, 2016;Haryanto, 2013;Putri et al, 2018), but other studies found that government spending did not affect or even was not associated with the decrease of economic growth (Basuki et al, 2019;Djohan 2016 et al). Di China, belanja pendidikan dan kesehatan berpengaruh pada perekonomian tetapi belanja modal tidak berpengaruh ( (Luintel et al, 2020) The difference in results might be caused by the quality of local government financial accountability. With more accountants and auditors, the country has better economic growth because its financial management is qualified (Abdolmohammadi & Tucker, 2002).…”
Section: Introductionmentioning
confidence: 99%